Lewis Bond journal - Bond, Lewis
Journal (92 pages; 1812 June 29-1813 May) kept by Major Lewis Bond during the War of 1812. Chronicles the battle of the River Raisin, Monroe, Mich., 1813.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: River Raisin, Battle of the, Monroe, Mich., 1813.; Michigan -- History -- War of 1812.; United States -- History -- War of 1812.; United States -- History -- War of 1812 -- Campaigns; Army officers